LIVING ALONGSIDE NATURE’S FURY: UNDERSTANDING VOLCANIC ERUPTIONS AND FLASH FLOODS - Habibullayeva Ayisha Hamidulla qizi,; Mannobov Abdumalik Mansurjon oʻgʻli, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from  Uzbekistan,  explores  two  of  the  most  awe-inspiring  yet  destructive  natural hazards on Earth — volcanic eruptions and flash floods. The author investigates the scientific causes behind each phenomenon, describes the scale of damage they can inflict on human lives and the environment, and outlines the essential precautions every person  should  know.  The  article  encourages  young  readers  to  view  disaster preparedness not as a burden, but as a vital life skill.